PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. WENANG PERMAI SENTOSA - MEWOH, ANFFERNEY DALLEN; Pio, Riane J.; Sumayku, Sontje (JURNAL ADMINISTRASI BISNIS, 2017)
PT. Wenang Permai Sentosa continues to create innovations and growth for corporate excellence. In connection with it is important for PT. Wenang Permai Sentosa to continue to maintain the progress and excellence of his company by creating organizational culture to be the basis, value and guidance for its employees (HR) which is as the main driver of the company in achieving business goals and profitability. With strong organizational culture owned by employees then the company will continue to grow and survive. In general, the results of the analysis states strongly agree to organizational culture and performance variables. This states the influence of organizational culture on the performance of employees of PT. Wenang Permai Sentosa is at a good level. With analysis test proved that Organizational Culture have positive effect on Employee Performance so that hypothesis accepted. So with the results of the authors concluded the factors that make the organizational culture effect on employee performance that employees have a commitment in the company and can work well with a team and understand what the company goals. The better the organization culture the employee has, the higher the employee's performance. Thus this study proves that Organizational Culture has a strong relationship to Employee Performance. Keywords : Organizational Culture, Employee Performance